Limitation of Acoustic Emission for Identifying Seeded Defects in Gearboxes - Tan, Chee Keong; Mba, David (Springer Science Business Media, 2005)
Acoustic Emissions (AE) is gaining ground as a Nonestructive Technique (NDT) for health diagnosis on rotating machinery. Vast opportunities exist for development of the AE technique on various forms of rotating machinery, including gearboxes. This paper reviews recent developments in application of AE to gear defect diagnosis. Furthermore, experimental results are presented that examine and explore the effectiveness of AE for gear defect diagnosis. It is concluded that application of AE to artificially seeded gear defect detection is fraught with difficulties, particularly for fault identification. In addition, the viability of the AE technique for gear defect detection by making observations from nonrotating components of a machine is called into question. Nevertheless, guidance is offered on applying the technique for monitoring the natural wear of gears.
Keywords: Acoustic emission